Shared Leadership and Team Performance. (August 2016) - Barnett, Robert C.; Weidenfeller, Nancy K.
The Problem: Shared leadership in teams has been the topic of substantial research in the last several years fueled, at least in part, by Pearce and Conger's helpful volume. The published literature is fragmented, complex, and difficult to navigate, making it challenging to quickly or easily gain a clear understanding of the progress that has been made and the findings that are relevant to shared leadership in teams. The Solution: This article describes and discusses recently published empirical evidence in an effort to summarize what is known about shared leadership in teams. Questions of shared leadership's effectiveness, what is shared, with whom, and how leadership is shared are addressed. The article concludes with a summary of what we now know about shared leadership and recommendations for Human Resource Development (HRD) professionals who are involved with or responsible for developing shared leadership in teams. The Stakeholders: This article is relevant to the interests of team leaders and members, organization managers, HRD professionals, and others who may be involved in promoting shared leadership and team effectiveness in their organizations.